Defining place identity: Misurata, Libya - Shinbira, Ibrahim (2017)
In the last few years, there has been growing attention given to the weakening of the place identity of many contemporary cities that have grown up as a result of rapid development and urban transformation. For this reason, place identity has been identified as one of the subject matters to consider in urban design in order to achieve good quality for future urban environments. In respect to this, over the past four decades, there has been a spate of attempts to reveal a wider understanding of place identity, particularly in relation to humans’ built environment relationships. To date, however, there have been relatively few attempts to integrate the concept of place identity into a more holistic theory of person-place relationship. Notions such as meanings and place attachment are rarely integrated with the physical characteristics in assessing place identity. Consequently, this research focuses on examining the influencing factors that are associated with place identity in the city centre of Misurata in Libya. This will be conducted using the three concepts of place as a multidimensional framework in defining place identity. The primary aim of the research is to examine place identity in light of the distinctive characteristics of place through identifiable place qualities as seen by the residents. Therefore, it is believed that, a qualitative inquiry is the best approach for this study; however, the quantitative methodology was also employed in this research in order to validate findings through triangulating the data. Accordingly, the research for this PhD has adopted a mixed methodological strategy in data collection and analysis. The techniques (methods) utilised for data collocation were survey, face-to-face interviews and mental mappings. The data analysis procedure was a rational-inductive approach based on the grounded theory strategy (data-led analysis). The research concludes that the main factors of person-place relationships (perception, meanings and attachment) significantly contribute to sustaining the place identity. The research demonstrates that there are seven characteristics of urban place that are strongly associated with place identity, as perceived by residents. These are imageability; visual quality; legibility; liveability; diversity; transparency and active frontages and walkability. These qualities were found as essential key performance criteria of urban place, evoking human perceptions and are important conditions for reinforcing place identity. The significance of meanings in fostering place identity was confirmed by seven identifiable factors, namely, place memory; life stage and place meaning; historical knowledge; symbolic meanings; likeable environment; a sense of belonging and pride; perceiving urban change and place meaning. Factors associated with place attachment were the emotional attachment; functional attachment; length of residence; familiarity and level of engagement. The main findings of this study confirm that both physical characteristics of place as an object component together with the meanings and attachment factors as subjective dimensions are important for sustaining place identity and creating a successful place in general. This study adds to the knowledge of the importance of understanding the complex layers of perceptions, meanings and attachment resulting from the person-place relationship in shaping places and sustaining place identity. In this regard, it also seeks to be part of the foundation or criteria to guide and formulate better urban design policy and innovative design for the future of Libyan towns and cities.